Age and Nutritional Status by Mini-Nutritional Assessment (MNA) can discriminate Alzheimer’s Disease Severity - Leandro-Merhi, Vania Aparecida; dos Santos, Tamires Barbosa Nascimento; Souza Tedrus, Gloria Maria de Almeida (International Journal of Advanced Engineering Research and Science, 2021)
Investigate the risk factors associated with Clinical Dementia Rating (CDR) in patients with Alzheimer's disease (AD). Cross-sectional study with 43 elderly people with AD. Parameters assessing nutritional status (anthropometry and mini-nutritional assessment-MNA), neurocognitive assessment and Clinical Dementia Rating (CDR) were investigated. For the investigation of AD severity risk factors, statistical analysis was performed using logistic regression models. The level of significance adopted was 5%. No statistically significant difference in the relationship between the parameters of anthropometry nutritional assessment and the CDR score were found. In the final regression model; only MNA (p=0.0159; OR=4.815; IC95%=1.342; 17.282) and age (p=0.0481; OR= 1.097; IC95%=1.001; 1.202), were associated with the severity of the disease (CDR). Age and MNA discriminate the severity of the disease and were considered risk factors for the severity of AD.